Numerical Study on Plastic Strain Distributions and Mechanical Behaviour of a Tube under Bending - Amaechi, C.V. (MDPI, 2022)
Tubular pipe structures have been used in various applicationsâdomestic, aviation, marine, manufacturing and material testing. The applications of tubular pipes have been considered greatly in the installation of tubular pipes, marine risers and pipe bending. For the investigation of plastic strains and the mechanical behaviour of a tube under bending, considerations were made utilising an exponent model with assumptions on the plane strain. The bending moment, wall thickness effect, cross-sectional distribution, stresses during bending and neutral layer boundaries were all presented as necessary theoretical formulations on the physics of tubular pipe bending. This model was based on the analytical and numerical investigation. In principle, the application can be observed as the spooling of pipes, bending of pipes and reeling. Comparisons were made on two models developed on the finite element analysis in Simscale OpenFEA, namely the linear-elastic and the elasto-plastic models. This study presents visualization profiles using plastic strain to assess its effect on the tubular pipes. This can increase due to the limitation of plastic deformation on the composite materials selected. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.